2020
DOI: 10.1016/j.neuron.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Therapy Targeting RAN Proteins Rescues C9 ALS/FTD Phenotypes in C9orf72 Mouse Model

Abstract: Highlights d Human antibodies recognize GA or GP RAN proteins with high affinity and selectivity d Human antibodies cross the blood-brain barrier and engage RAN protein targets in vivo d a-GA 1 antibody reduces GA, GP, and GR levels in C9 models d a-GA 1 improves behavior and survival and decreases neurodegeneration in C9-BAC mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 62 publications
3
65
3
Order By: Relevance
“…We cannot exclude that poly‐GA expression triggers additional indirect effects in vivo , for example by directly releasing other molecules that promote TDP‐43 aggregation in neighboring cells or triggering release of such factors from glial cells. Our findings provide mechanistic insights into very recent active and passive antibody therapy approaches in C9orf72 mouse models by us and others (Nguyen et al , ; Zhou et al , ). Nguyen et al () also reported that anti‐GA antibodies partially restore proteasome function in poly‐GA‐expressing cells and show that antibodies clear poly‐GA via the proteasome and autophagy pathway depending on the intracellular Fc‐receptor TRIM21.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We cannot exclude that poly‐GA expression triggers additional indirect effects in vivo , for example by directly releasing other molecules that promote TDP‐43 aggregation in neighboring cells or triggering release of such factors from glial cells. Our findings provide mechanistic insights into very recent active and passive antibody therapy approaches in C9orf72 mouse models by us and others (Nguyen et al , ; Zhou et al , ). Nguyen et al () also reported that anti‐GA antibodies partially restore proteasome function in poly‐GA‐expressing cells and show that antibodies clear poly‐GA via the proteasome and autophagy pathway depending on the intracellular Fc‐receptor TRIM21.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings provide mechanistic insights into very recent active and passive antibody therapy approaches in C9orf72 mouse models by us and others (Nguyen et al , ; Zhou et al , ). Nguyen et al () also reported that anti‐GA antibodies partially restore proteasome function in poly‐GA‐expressing cells and show that antibodies clear poly‐GA via the proteasome and autophagy pathway depending on the intracellular Fc‐receptor TRIM21. Moreover, boosting proteasome function in donor and receiver cells with small molecules such as rolipram may overcome poly‐GA‐induced proteasome impairment and lead to clearance of ubiquitinated substrates such as TDP‐43.…”
Section: Discussionsupporting
confidence: 68%
“…These C9-BAC mice were recently used to demonstrate that a human antibody targeting the GA RAN protein is sufficient to rescue behavior and survival phenotypes, without changing the levels of their corresponding expansion RNAs. These preclinical data highlight the therapeutic potential of targeting RAN proteins (Nguyen et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Similar to our previously published data on mice with shorter repeat tracts (29-37 repeats) (Liu et al, 2016), sense and antisense RNA foci were not detected in animals in the C9-50 line (Fig 5A, B). Next, we compared RAN protein aggregates in the retrosplenial cortex by immunohistochemistry (IHC) or immunofluorescence (IF) using human α-GA1 and α-GP1 antibodies (Nguyen, Montrasio et al, 2020) (Fig 5C, S8A). At 40 weeks of age, there was a significant increase in percentage of cells with polyGA aggregates (71% vs 40%) and polyGP aggregates (22% vs. 15%) detected by IHC or IF in the C9-800 compared to the C9-500 mice (Fig 5C-E) while no GA or GP aggregates were detected in the C9-50 sub-line consistent with the decreased penetrance in this sub-line.…”
Section: Bac Micementioning
confidence: 99%
“…To remove any traces of disordered hSOD1 in the native samples we performed two sequential incubations (1′ and 2′) of each sample. Input (1/200th of total input), non-bound (n.b., 1/200th of sample) and immunocaptured (i.c., 1/200th of sample) fractions were immunoblotted using rabbit antibody targeting aa 24-39 of hSOD1 (rbAb αSOD1 [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Figure S1a for a full view of the filter. f The human SOD1 (hSOD1) peptide sequences used for immunization aligned to the murine SOD1 (mSOD1) epitope sequences.…”
Section: Verification Of Mab Binding To Spinal Cord-derived Hsod1 Aggmentioning
confidence: 99%